Blockchain adoption in sustainable supply chains: Opportunities, challenges, and sustainability impacts across sectors - Md Jawadur Rahim; Md. Jahidul Islam; Subroto Deb Nath; Muhammad Ihsan Ibn Rahim; Ather Yeasir (Annals of Human Resource Management Research, 2024)
Purpose: This study reviews the integration of blockchain technology into modern financial systems and outlines its huge potential to improve transparency, security, and operational efficiency. Based on the challenges of data integrity, fraud prevention, and the reduction of intermediaries, this study assesses the transformational role of blockchain in financial institutions. Research Methodology: A mixed-methods approach was used, combining quantitative survey data from 150 financial executives with qualitative insights from expert interviews. Statistical analysis and thematic interpretation were used to provide an integrated assessment of blockchain applications and the challenges of its adoption in the financial sector. Results: The results show that blockchain improves transaction transparency and security, reducing fraud and data manipulation. Respondents were optimistic about cost reductions from eliminating intermediaries. However, adoption remains limited by scalability issues, regulatory uncertainty, and technical integration challenges, which hinder broader implementation. Conclusions: Blockchain offers strong potential to enhance transparency, security, and efficiency in financial systems; however, adoption remains limited due to complexity, high costs, and regulatory challenges. Limitations: The limitations of the study are the small sample size, which limits the generalization of findings. Further research with larger and more diverse samples is needed to investigate more comprehensively the impact of blockchain on the financial sectors. Contributions: Therefore, this research contributes to the discourse on blockchain as a transformative finance technology by providing insights into useful strategic, policy, and technology issues. Novelty: It also presented both opportunities and challenges in view of realizing blockchain's role in digitizing financial ecosystems.